A global assessment of the economic effects of export taxes - Laborde Debucquet, David; Estrades, Carmen; Bouët, Antoine (International Food Policy Research Institute, 2013)
This study has been undertaken to understand and evaluate the potential negative consequences of export taxes which are implemented by many countries today and which are not disciplined by any international agreement. This paper uses a new detailed global dataset on export taxes at the HS6 (Harmonized System 6 level) level and the MIRAGE (Modeling International Relationships in Applied General Equilibrium) global computable general equilibrium model to assess the impact of export taxes on the world economy. We find that limitations on export taxes would have worldwide effects: the average export tax on global merchandise trade was 0.48 percent in 2007, with the bulk of these taxes imposed on energy products. The removal of these taxes would increase global welfare by 0.23 percent, which is a larger figure than the expected gains from the World Trade Organization’s Doha Development Round.